2013
DOI: 10.1111/scd.12015
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual disability and impact on oral health: a paired study

Abstract: The objective was to assess the oral health status, the treatment needed, and the type of dental health services access of intellectually disabled (ID) subjects in Teresina, Brazil. The sample consisted of 103 ID subjects matriculated in centers for special needs people and 103 siblings. Results were analyzed using paired t-test, chi-square test, and odds ratio. ID subjects had fair (63.1%; p < .001) and their siblings had a good oral hygiene (n = 103 [55.3%]; p < .005). ID had more decayed (3.52; p < .005), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 12 publications
4
54
2
5
Order By: Relevance
“…The low contribution of the filled component observed in our study is an observation that has also been reported by previous studies and may be reflective of the overall lower provision of dental treatment to the intellectually disabled than the general population (and hence the greater progression of carious lesions) and also to the tendency for extractions rather than restorations due to difficulties in the behavioural management of this population [5,25,32]. Exceptionally, in an assessment of more than 4,000 adult intellectually disabled persons in the United States, Morgan et al [6] reported very low scores for decayed teeth and a high predominance of filled teeth.…”
Section: Discussionsupporting
confidence: 85%
“…The low contribution of the filled component observed in our study is an observation that has also been reported by previous studies and may be reflective of the overall lower provision of dental treatment to the intellectually disabled than the general population (and hence the greater progression of carious lesions) and also to the tendency for extractions rather than restorations due to difficulties in the behavioural management of this population [5,25,32]. Exceptionally, in an assessment of more than 4,000 adult intellectually disabled persons in the United States, Morgan et al [6] reported very low scores for decayed teeth and a high predominance of filled teeth.…”
Section: Discussionsupporting
confidence: 85%
“…[14] This is consistent with many previous studies which reported poorer standard of oral hygiene and greater prevalence of periodontal diseases in DS children than their normal counterparts. [512151617181920] A multitude of factors may be involved in the increased susceptibility to gingival and periodontal diseases among individuals with DS. [21] Factors previously investigated include mental retardation, subgingival plaque composition, immune/inflammatory responses, and others.…”
Section: Discussionmentioning
confidence: 99%
“…[644] This phenomenon may be the result of the tendency for emergency extractions (because of delayed seeking of treatment) or due to difficulties in behavioral management during dental procedures favoring measures that are less technique sensitive such as the extraction of teeth rather than their restoration. [63345]…”
Section: Discussionmentioning
confidence: 99%